2016
DOI: 10.1016/j.celrep.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

DIGIT Is a Conserved Long Noncoding RNA that Regulates GSC Expression to Control Definitive Endoderm Differentiation of Embryonic Stem Cells

Abstract: Long noncoding RNAs (lncRNAs) exhibit diverse functions, including regulation of development. Here we combine genome-wide mapping of SMAD3 occupancy with expression analysis to identify lncRNAs induced by activin signaling during endoderm differentiation of human embryonic stem cells (hESCs). We find that DIGIT is divergent to Goosecoid (GSC) and expressed during endoderm differentiation. Deletion of the SMAD3-occupied enhancer proximal to DIGIT inhibits DIGIT and GSC expression and definitive endoderm differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 62 publications
(79 reference statements)
2
91
2
Order By: Relevance
“…BRD3 -/cells showed reduced SOX17 expression on the periphery of differentiating colonies as well as an expansion of central cells staining for SOX2 ( Figure 4E). These results demonstrate that loss of BRD3 inhibits endoderm differentiation, a phenotype also observed with depletion of DIGIT (Daneshvar et al, 2016). (A) Strategy for depletion of BRD3 in hESCs using the CRISPR/Cas system and a homology plasmid to insert a puromycin resistance cassette and stop codon into the first exon of BRD3 (top).…”
Section: Brd3 Regulates Definitive Endoderm Differentiationmentioning
confidence: 88%
See 1 more Smart Citation
“…BRD3 -/cells showed reduced SOX17 expression on the periphery of differentiating colonies as well as an expansion of central cells staining for SOX2 ( Figure 4E). These results demonstrate that loss of BRD3 inhibits endoderm differentiation, a phenotype also observed with depletion of DIGIT (Daneshvar et al, 2016). (A) Strategy for depletion of BRD3 in hESCs using the CRISPR/Cas system and a homology plasmid to insert a puromycin resistance cassette and stop codon into the first exon of BRD3 (top).…”
Section: Brd3 Regulates Definitive Endoderm Differentiationmentioning
confidence: 88%
“…Error bars represent standard deviation of three replicates. (B) The table shows normalized RPKM values for expression of BRD2, BRD3, and BRD4 with endoderm differentiation(Daneshvar et al, 2016). (C) qRT-PCR shows the enrichment DIGIT (left) and MALAT1 (right) following immunoprecipitation of BRD2, BRD3, and BRD4 proteins on day 4 of endoderm differentiation.…”
mentioning
confidence: 99%
“…To the best of our knowledge, only one literature to date has reported about DIGIT, in which DIGIT was identified as a key regulator of human and mouse definitive endoderm differentiation. 13) In this study, we demonstrated that DIGIT silence significantly reduced cell viability, migration, tube-like structures formation, and also induced apoptosis of HMEC-1 cells, implying the pro-growth, promigratory, and pro-angiogenic roles of DIGIT in endothelial cells.…”
Section: Discussionmentioning
confidence: 49%
“…DIGIT is divergently transcribed from the mesendoderm regulator GSC, and is required for productive endoderm differentiation of both human and mouse embryonic stem cells. 13) Interestingly, endothelial cells originate from the endoderm. 14) Based on these reasons, we speculated that DIGIT may play a regulatory role in endothelial cells angiogenesis.…”
mentioning
confidence: 99%
“…In fact, lncRNA-21A, UCA1 and AK023948 were successfully knockout in cancer cell lines using CRISPR-Cas9. In addition, Daneshvar and co-workers demonstrated that a sequence encoding GFP followed by a poly (A) signal was inserted to the downstream of the Divergent to GSC, induced by TGF-β family signaling (DIGIT) transcription start site using CRISPR-Cas9 system [94]. The insertion of cassette allowed for the induction of transcription of GFP at the DIGIT locus but led to termination at the poly(A) signal, resulting in disrupting full length DIGIT expression.…”
Section: Crispr/cas9 Genome Editing Techniquementioning
confidence: 99%